A novel supramolecular AIE gel acts as a multi-analyte sensor array. (16th October 2018) - Yao, Hong; Wang, Jiao; Song, Shan-Shan; Fan, Yan-Qing; Guan, Xiao-Wen; Zhou, Qi; Wei, Tai-Bao; Lin, Qi; Zhang, You-Ming
Abstract : Supramolecular gelatorWJ could form a stable supramolecular organogel (WJG ) with strong aggregation-induced emission (AIE). Utilizing the AIE gel, we successfully developed a multi-analyte sensor array which could accurately identify CN −, Al 3+, and Fe 3+ andl -Cys. Abstract : A novel organic gelator (WJ ) based on benzimidazole and acylhydrazone naphthol moities has been designed and synthesized. The organic gelator (WJ ) could form a stable organogel (WJG ) with strong aggregation-induced emission (AIE). Interestingly, theWJG shows multi-stimuli-response for many analytes such as CN −, Al 3+ and Fe 3+ andl -Cys. Therefore, a multi-analyte sensor array based onWJG has been successfully developed. TheWJG presents selective fluorescent and colorimetric response for CN − . Meanwhile, theWJG could selectively identify Fe 3+ and Al 3+ in the gel state. With the addition of Fe 3+ the yellow-green AIE ofWJG was quenched. In addition, the AIE ofWJG could be selectively recovered by addingl -Cys. So the AIE presents an "on–off–on" type by alternatively adding Fe 3+ andl -Cys. Moreover, upon the addition of Al 3+, the yellow-green AIE ofWJG shows a blue shift and changes to blue. The detection limits of the sensor array for CN −, Al 3+ and Fe 3+ are 3.02 × 10 −6 M, 5.78 × 10 −8 M, and 3.81 × 10 −9 M, respectively. TheWJG could act as a multi-analyte detection and fluorescent display material.